HUBUNGAN ANTARA NABI DENGAN AGAMA SAMAWI - St. Hadidjah (State Institute of Islamic Studies (IAIN) Palu, 2006)
Muslims believe that Muhammed is the last prophet whom God sent to all people of the world. However, they also believe in all prophets sent before Muhammed. The difference laies only the people on whom the prior prophets sent. All prophets prior to Muhammad were sent for certain people only, but Muhammad was sent to all people of the word. Based on this, the problem is what the relationship is between Muhammed and the revealed religions prior to him. This article discusses that point.Kata Kunci : Nabi, agama samawi, fitrah